Envejecimiento activo y las funciones ejecutivas en los adultos mayores del Centro de Salud Tipo C, Buena Fe - Betancourt Zambrano, Shirley Vanessa (2019)
Active aging is a condition established by public health organizations such as the course where all the biopsychosocial aspects of the elderly are optimized, so that this process is of significant contribution in areas such as daily living, quality of life speaking globally in the course of his life and his normal life cycle. On the other hand, executive functions play a fundamental role in the process of optimizing active and healthy aging, so these are the set of abilities that the individual has to generate processes such as decision-making, analyzing, acting etc. The executive functions are nothing more than the essence of our behavior and the generator of several essential cognitive processes so that the human being can interact and fend for himself within the biological, psychological and social areas. The main objective of this research project is to establish how active aging influences the executive functions of older adults in the C-Buena Fe Health Center, year 2019. As a proposal, the intervention of a strategic plan based on workshops that generate cognitive stimulations suitable for specific areas such as executive functions in older adults will have an incidence scope and determine how with these workshops the functions could prevail obtaining a globally consolidated active aging in all areas